Efektivitas Pengayaan Daphnia sp. dengan Viterna Untuk Post Larva Ikan Papuyu (Anabas testudineus Bloch) - Siswanto, Siswanto; Aminah, Siti; Sofarini, Dini; Nopitasari, Nopitasari (Universitas Trunojoyo Madura, 2023)
In the development of climbing perch cultivation, there are several factors that are still obstacles, namely, slow growth and low survival, especially in the critical period phase, namely the post-larval phase. The aim of this research was to analyze the effectiveness of giving Daphnia sp with viterna enrichment on the survival and growth of climbing perch post-larval. Proximate analysis was carried out at the end of the research to see the nutritional content of the enriched Daphnia sp. Sampling was carried out at the beginning and end of the study with a maintenance period of 30 days. During rearing the larvae were given Daphnia sp 2 times a day. This study used RAL for 4 treatments and 3 repetitions, namely: treatment A (control), B (viterna enrichment 10 ml/l), C (viterna enrichment 20 ml/l) and treatment D (viterna enrichment 30 ml/l). The proximate test results showed that treatment B produced the highest protein content, namely 59.61%, while the control treatment was 49.45%. Survival rates range between 76-88%. Relative weight growth ranged between 214.41-524.69% while relative length ranged between 29.24-59.62%. Treatment B produced the best relative growth in weight and length but was not statistically significantly different from the other treatments. Treatment D produced the best survival but after statistical tests it was not significantly different between treatments.